Coexpression of EphA10 and Gli3 promotes breast cancer cell proliferation, invasion and migration. (14th May 2021) - Peng, Jing; Zhang, Danhua
Abstract : This study investigated the influences of EphA10 and Gli3 on breast cancer (BC) cell proliferation, invasion and migration. Immunohistochemistry was used to reveal the expressions of EphA10 and Gli3 in 18 intraductal carcinomas, 124 invasive carcinomas, 50 paracancerous tissues (2 cm away from the tumor, when possible or available), 50 lobular hyperplastic tissues and 30 normal breast tissues. qRT-PCR and Western blotting were applied to detect the expressions of EphA10 and Gli3 in invasive BC cells (MDA-MB-231, BT20 and Hs578T) and normal human mammary epithelial cells (MCF10A). MDA-MB-231 and BT20 cells were transfected with sh-EphA10, sh-Gli3 or sh-EphA10+sh-Gli3. CCK-8 was used to test the proliferation of transfected MDA-MB-231 and BT20 cells. Transwell and scratch assays were used for evaluation of invasion and migration of the transfected cells. EphA10 and Gli3 were highly expressed in invasive carcinomas and invasive BC cells. The expressions of EphA10 and Gli3 were associated with the clinicopathological characteristics and poor prognosis of patients with invasive BC. Knockdown of EphA10 or Gli3 suppressed activities of BC cells. Knockdown of both EphA10 and Gli3 was more effective than knockdown of Gli3 alone. Taken together, coexpression of EphA10 and Gli3 promotes BC cell proliferation, invasion and migration.